Multilateral International Treaties Ensuring Water Security in Central Asia - Zh. M. Amanzholov (Московский журнал международного права)
Water security is an indispensable part of ecological security and to ensure it states of the region of Central Asia will have to change their respective approaches to the problem of shortage of water resources in the region in accordance with rules contained in international treaties. The state practice proves that only through execution and proper implementation of relevant international treaties the problems of the kind were successfully solved. In the case of the Central Asian states, one of the major facts hindering the solution of this problem is insufficient implementation or nonimplementation of international legal principles and norms in regard of the use and protection of transboundary water resources. This is due to the fact that some states are not Parties to the most important international treaties concerning this issue. Though there are no substantial reasons for the Central Asian states to avoid these treaties, as they are completely applicable to the situation in the region. It is important to remark that apart from issues of transboundary resources, protection of wild species should also be considered in this regard.The other problem here is insufficient internal legislation of the states in respect of these issues. Sometimes provisions contained in them contradict international treaties and are implemented intentionally in order to receive maximum benefit out of the use of transboundary resources.In the conclusion it is necessary to state that there are no comprehensive international legal norms regulating all the aspects related to transboundary resources. But still in order to ensure the security of water resources Central Asian states have to adhere to relevant international treaties as this will not only help to stabilize the situation but also will allow the states to use the international expertise in this sphere to the full extent.